(3EYdGe GdCYdGe ajef HhjY bHd GdGMJdGe ef edhc Ojf GdGSdGes - (3CHhYHO Gddg eMeO Hf YHO Gddg Hf SYjO GdSdeGfi GdZQfGWi GdCfOdSj, GdTgjQ HdSGf GdOjf Hf GdNWjH,J (B776 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GPj HOC GdNdb Ke jYjOg , hhYO GdhYjO hdG jNda hYO hhYjOg s
(3BNQgG (B:s
(3OhdI GdCejQ YHO GdeDef GHf Ydi ChdGO GdehMOjf Ke cGfJ HjYI GdYGeI EjGg jhe GdLeYI s
(3GdfSNI HgG MhGTs
(3HBNQg (B: (3GfJgi eG hLO ef JGQjN EYdGe GdCYdGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3eJaQbGJs